Global physical climatology - Hartmann, Dennis L. (Elsevier, 2016)
"Global Physical Climatology, Second Edition, provides an introduction to the science of climate and climate change. It begins with a basic introduction to the climate system, and then introduces the physics of the climate system, including the principles and processes that determine the structure and climate of the atmosphere, ocean, and land surface. This basic knowledge is then applied to understanding natural variability of the climate in both the present and past, the sensitivity of climate to external forcing, explanations for the ice ages, and the science of human-induced climate change. The physical principles and computer models necessary for understanding past climate and predicting future climate are introduced."--Publisher's website.